A relação professor/livro didático no ensino-aprendizagem de Língua Portuguesa na 4ª série do ensino fundamental - OLIVEIRA, Márcia Andréa Almeida de (2007)
In this thesis, we aimed at investigating the relationship between teacher and textbook in the 4th grade of six K12 schools, located in the Belém. We investigated the criteria used in the process of choosing materials, in the teaching objects prioritized in the textbook and in the Portuguese classes, in the sections used and the strategies introduced by teachers when they use the textbooks. In this study, we adopted a research of ethnographic character because we considered the teachers voices in the process of choosing and using of the books in the classroom. We also used the sociointeractionism ideas of Vygotsky (1984, 2003) and Bakhtin (1993, 1997, 1999) about language, interaction, construction of the subject and so on, and we used some studies related to Portuguese teaching and to textbooks. In the data analysis, we reflected on textbook activities (published between 2003 and 2005) related to the understanding and the prodution (oral and written) and on the teaching objects prioritized in each book. Furthemore, we analyze the six teachers interviews and their Portuguese classes, and we compared the textbooks proposals with the teachers proposals and we presented some suggestions to improve the use of the books. Results show that textbooks, adopted by schools in this study, seem not to play the directive role in the teaching neither assume the teachers role because they are only used to complement activities, previously designed by them.